Tuber Yield and Quality of Two Potato Cultivars in Response to Nitrogen Fertilizer Management - Assunção, Natália S. [UNESP]; Fernandes, Adalton M. [UNESP]; Soratto, Rogério P. [UNESP]; Mota, Lydia Helena S. O. [UNESP]; Ribeiro, Nathalia P. [UNESP]; Leonel, Magali [UNESP] (Springer Nature, 2020)
In Brazil, the potato cultivar Agata is used for fresh market, while the cultivar Markies is used for both fresh market and frying industry. However, these cultivars may respond differently to nitrogen (N) management. Thus, field experiments with these cultivars were conducted to evaluate marketable tuber yield and physico-chemical and nutritional quality of tubers in response to four different early N managements (80p: 80 kg N ha−1 at planting; 160p: 160 kg N ha−1 at planting; 40 + 120: 40 kg N ha−1 at planting plus 120 kg N ha−1 at hilling; and 80 + 80: 80 kg N ha−1 at planting plus 80 kg N ha−1 at hilling) combined with late N application rates at tuber bulking stage (0, 20, 40 and 80 kg N ha−1). For both cultivars, the application of only 80 kg N ha−1 at planting was enough to have satisfactory marketable tuber yield and the late N application did not provide benefit to yield. The 80 + 80 treatment reduced the concentrations of starch and carbohydrate and increased the protein concentration in tubers of cultivar Agata, and promoted the Ca biofortification of tubers in both cultivars. Tuber Fe concentration of cultivar Agata was higher with the 80p treatment. The early N managements with N supplied at planting increased tuber Cu concentration of both cultivars. Late N application increased the concentration of protein, Ca and Fe only in the Agata tubers. For cultivar Markies, the tuber reducing sugar concentration was increased by the late application of 40 kg N ha−1 combined with the early N application treatments 160p and 40 + 120, but only small variations in the colour intensity or yellow tonality of the fried potatoes were observed.
Keywords: Fried potatoes; Marketable tuber yield; Nutrient management; Solanum tuberosum; Tuber physico-chemical properties